2021
DOI: 10.3390/s21093059
|View full text |Cite
|
Sign up to set email alerts
|

Conservative Quantization of Covariance Matrices with Applications to Decentralized Information Fusion

Abstract: Information fusion in networked systems poses challenges with respect to both theory and implementation. Limited available bandwidth can become a bottleneck when high-dimensional estimates and associated error covariance matrices need to be transmitted. Compression of estimates and covariance matrices can endanger desirable properties like unbiasedness and may lead to unreliable fusion results. In this work, quantization methods for estimates and covariance matrices are presented and their usage with the optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…An alternative strategy for reducing the communication load is to quantize the data to be exchanged, see, e.g., [124,152,172]. A key aspect of quantization in DSN is how to preserve conservativeness when the communicated data is quantized [63,64]. In this thesis, however, it is assumed that quantization effects can be neglected.…”
Section: Communication Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…An alternative strategy for reducing the communication load is to quantize the data to be exchanged, see, e.g., [124,152,172]. A key aspect of quantization in DSN is how to preserve conservativeness when the communicated data is quantized [63,64]. In this thesis, however, it is assumed that quantization effects can be neglected.…”
Section: Communication Managementmentioning
confidence: 99%
“…The problem is to fuse (y 1 , R 1 ) and (y Ψ , R Ψ ). The scenario is parametrized in ρ ∈ [0, 1] according to (64,32,16,8,4,2) , The quantity ρΓ −1 is interpreted as common information. By construction,…”
Section: Simulation Specificationsmentioning
confidence: 99%
“…In parallel, relevant scholars also carried out relevant research on the application of covariance intersection to the above-mentioned filter. At this stage, covariance intersection is mainly applied to the Kalman filter [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. Qi, W. [ 25 ] (2020) applied BCI fusion and fast SCI fusion to a time-varying Kalman filter in their research and suggested that this method should solve the high-dimensional nonlinear optimization problem; however, the algorithm’s operation implies great computational complexity and quantity.…”
Section: Introductionmentioning
confidence: 99%